SURTO DE LAGARTAS EM Eucalyptus spp. (MYRTACEAE) NO ESTADO DE MATO GROSSO OUTBREAK OF CATERPILLARS ON Eucalyptus spp. (MYRTACEAE) IN THE STATE OF MATO GROSSO, BRAZIL - Peres Filho, OtÃ¡vio; Klein, H.; Berti Filho, Evoneo (REVISTA DE AGRICULTURA, 2015)
SURTO DE LAGARTAS EM Eucalyptus spp. (MYRTACEAE) NO ESTADO DE MATO GROSSO OUTBREAK OF CATERPILLARS ON Eucalyptus spp. (MYRTACEAE) IN THE STATE OF MATO GROSSO, BRAZIL